Germination and seedling growth of Trichloris crinita (Lag.) Parodi under water stress conditions (Semiárida, 2017)
Argentine Natural grasslands of Argentina show a degraded condition due to inadequate management practices applied over several years. Many native species are in the process of experimentation as perennial cultivated pastures. One of them is Trichloris crinita, a warm-season perennial grass of good forage quality, which is adapted to natural conditions of environmental stress. Its distribution in Argentina ranges from very arid to sub-humid climates. The aim of this study was to evaluate, in greenhouse conditions, the response of populations of T. crinita from the Caldenal (Prosopis caldenia forest), Monte (shrubland) and ecotone Caldenal - Monte to water stress during germination and plant growth. Variables evaluated at the germination stage were germination capacity, rate and average time of germination, and recovery after water stress. At the initial plant growth stage, relative water content, dry weight of aerial and root biomass and the relationships among them were assessed. A differential behavior was observed among populations. Under the controlled conditions assayed, Caldenal populations were better suited to stress at germination. A population of Santa Rosa site of Caldenal showed better adaptation to drought at growth stage (113 days from sowing). This information is essential to select the most suitable populations to be used in restoring plans for degraded rangelands of the semiarid and arid Pampean Region of Central Argentina. DOI: http://dx.doi.org/10.19137/semiarida.2016(02).39-54
Keywords: natural grassland; perennial grass; drought; restoration